MELATI (MERAWAT PREMATUR SEPENUH HATI) EDUCATION BASED ON FAMILY CENTERED CARE IN THE STIMULATION, MONITORING, AND DETECTION OF PREMATURE BABY DEVELOPMENT - Amaliya, Sholihatul; Kapti, Rinik Eko; Azizah, Nurona; Supriati, Lilik; Ulya, Ikhda (Caring: Jurnal Pengabdian Masyarakat, 2024)
Complications and risks of short- and long-term morbidity will affect the development and growth of premature babies. Mother's knowledge affects the ability and confidence in monitoring the growth of mothers with premature babies that can be enhanced through the provision of health education. The health education given needs to empower mothers to perform stimulation, monitoring, and detection of the growth of premature babies properly. This community service activity is conducted with the aim of knowing the impact of health education on knowledge and the ability of mothers in giving stimulation to premature babies with the media educational booklet entitled MELATI. The service activity was conducted in Malang Raya region in July to October 2023 with the instrument of questionnaire and observation sheet development examination (KPSP). The educational activities are conducted in two phases with a duration of 60 minutes each. The evaluation of the activities is carried out one week after the educational activity by re-measuring the knowledge and sensitivity of mothers in stimulation, monitoring, and early detection of the growth of premature babies. As a result of this activity, the proportion of mothers with knowledge and skills both before intervention is 5% and after intervention 90%. Interventions of health education with the MEDIA booklet MEDIA can enhance the knowledge and skill of the mothers in stimulation, monitoring, and detection of the growth of premature babies. MELATI booklet can be used as one of the media providing education to mothers who have a premature baby.